Efficacy and safety of lixisenatide in elderly ( ≥65 years old) and very elderly ( ≥75 years old) patients with type 2 diabetes: an analysis from the GetGoal phase III programme1. Issue 2 (16th September 2014) - Raccah, Denis; Miossec, Patrick; Esposito, Virginie; Niemoeller, Elisabeth; Cho, Meehyung; Gerich, John
Abstract Background The objective of this article is to evaluate the pharmacokinetics, efficacy and safety of lixisenatide (subcutaneous injection) in elderly (≥65 years old) and very elderly (≥75 years old) patients with type 2 diabetes mellitus. Methods We conducted a phase I, single‐centre, open‐label study to evaluate the safety and pharmacokinetics of a single lixisenatide 20 µg dose and a pooled analysis of six randomized, placebo‐controlled, phase III studies (12‐month or 24‐month duration) that evaluated glycaemic parameters and safety in patients receiving lixisenatide 20 µg once daily or placebo. Results The pharmacokinetics study included 36 healthy subjects, including 18 elderly healthy subjects (≥65 years old) and 18 matched young healthy subjects (18–45 years old). The pooled analysis included 3188 patients, including 2565 patients <65 years old and 623 patients ≥65 years old (including 79 patients ≥75 years old). Mean exposure with lixisenatide 20 µg was ~30% higher in elderly than in young subjects, and the terminal half‐life was prolonged by ~1.6 times. Maximum concentration (Cmax) and time to Cmax (tmax) were comparable in both groups. Equal numbers of elderly and young subjects reported treatment‐emergent adverse events, the majority of which were gastrointestinal disorders. In the pooled analysis, lixisenatide 20 µg once daily provided significant reductions in HbA1cversus placebo for all age groups. There was a similar incidence of treatment‐emergent adverse events across all age groups (range: 69–73%). The incidence of symptomatic hypoglycaemia was generally comparable between lixisenatide‐treated and placebo‐treated patients. Conclusion These data suggest that lixisenatide is effective and well tolerated in elderly and very elderly patients with type 2 diabetes mellitus. © 2014 The Authors. Diabetes/Metabolism Research and Reviews published by John Wiley & Sons, Ltd.